The lucky one - Sparks, Nicholas (USA : Grand Central Pub, 1998)
U.S. Marine Logan Thibault believes he's found a lucky charm buried in the sands of Iraq: a photograph of a smiling woman. The chain of events that leads to him possessing the photograph and finding the woman pictured in it is the stuff of love stories.
Keywords: U.S. Marine Story-Fiction; Divorce Woman-Fiction; Lucky charm -- Fiction; North Carolina --Fiction.